The Strategic Role of Information Technology Leadership in Indonesia Stock Exchange - Aditya Reza Firdaus; Rizal Fathoni Aji; Yosephine Novianti (AI Society & STMIK Indonesia, 2024)
Information Technology involvement on an organization may vary. Based on McFarlan’s IT strategic impact grid, it is being classified to be support, factory, turnaround, and strategic. Each quadrant has a different IT leadership position and IT role. PT Bursa Efek Indonesia (IDX) is an institution with high dependency on IT, as they manage online activities, use website, and enter global market. This qualitative study focuses on IDX’s IT leadership implication and role of IT on the system used. The data collection was carried out by exploratory literature studies and semi-structured interview. The findings of this study show that IDX is now in the strategic quadrant. It depicts from McFarlan application mapped which shifts to focus on strategic as The Role of IT, also dominant quadrant category of IT Leadership Implication is strategic.